2017
DOI: 10.1002/aoc.3852
|View full text |Cite
|
Sign up to set email alerts
|

Acridine‐containing RuII, OsII, RhIII and IrIII Half‐Sandwich Complexes: Synthesis, Structure and Antiproliferative Activity

Abstract: Research aimed at enhancing the efficacy of organometallic complexes against cancer, has shown that attaching bio-active molecules to (metallo)drugs often enhances their biological properties. New salicylaldimine and 2-pyridylimine ligands (L2 and L3), containing a bio-active acridine scaffold, were synthesized and complexed to Rh(III), Ir(III), Ru(II) and Os(II) metal ion centers. The resulting acridine-containing half-sandwich complexes have been characterized fully by elemental analysis, FT-IR and NMR spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Half-Sandwich complexes such as [(η 6 -arene)M(L)Cl] + have demonstrated good anticancer activity through multimodal binding with DNA [ 14 , 15 ]. Interestingly, one such complex, RAPTA-C, is an antimetastatic, antitumoral and antiangiogenic drug candidate with the potential of reaching clinical evaluation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Half-Sandwich complexes such as [(η 6 -arene)M(L)Cl] + have demonstrated good anticancer activity through multimodal binding with DNA [ 14 , 15 ]. Interestingly, one such complex, RAPTA-C, is an antimetastatic, antitumoral and antiangiogenic drug candidate with the potential of reaching clinical evaluation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their anti‐proliferative activity was evaluated on the HL‐60 (blood cancer) cell lines, and the effective results were obtained ( Table 35). Compound 67 exhibited most effective anti‐proliferative activity [134] …”
Section: Recent Advancements In the Metal Complexes As Anticancer Agentsmentioning
confidence: 99%
“…Following the work made in the Sadler and Dyson research groups, a number of further (arene)Ru(II)-based compounds have been identified as potential candidates for clinical development [1][2][3][4][5][6][7]. Although, considerably less experimental data have been published for the isoelectronic (arene)Rh(III) compounds, several (η 5 -Cp*)Rh(III) complexes exhibit higher in vitro activity than the related Ru(II) complexes or even cisplatin, at least against selected cancer cell lines [8][9][10][11][12][13][14][15][16][17]. In addition, its optimal ligand exchange kinetics make (η 5 -Cp*)Rh(III) cation suitable drug delivery system for cytotoxins that are too toxic to be delivered directly, or have poor pharmacokinetics, such as curcumin [18].…”
Section: Introductionmentioning
confidence: 99%